Understanding how environmental heterogeneity and elevation drives the distribution of woody communities across vegetation types within the campo rupestre in South America - Bueno, Marcelo Leandro; Rezende, Vanessa Leite; De Paula, Luiza Fonseca A.; Meira-Neto, João Augusto Alves; Pinto, José Roberto Rodrigues; Neri, Andreza Viana; Pontara, Vanessa (Journal of mountain science, 2021)
The campo rupestre sensu lato is a vegetation type that occurs in South American mountains, supports a distinctive flora characterized by high rates of endemism, high herbaceous species richness and often-neglected but also species-rich of the arboreal stratum. We aimed to investigate how environmental factors and elevation are associated with the distribution and diversity of woody species in different rupestrian vegetation types across South America. Using a database of 2,049 woody species from 185 sites across four vegetation types within the campo rupestre , we assessed how the vegetation types were grouped according to their floristic composition and number of shared indicator species, as well as by using different beta diversity indices. The most important variables from a set of 27 variables (e.g. altitude, geo-edaphic and climatic) explaining species distribution were identified using redundancy analysis (RDA) and variation partitioning methods. The distribution of vegetation types was related to both environmental and spatial fractions, with a set of 17 variables retained (e.g. rockiness, grass cover and temperature seasonality as the most important variables). There was an association between the floristic composition of each vegetation type and the elevation range. Although the identified vegetation types are floristically related, they are distinguished by exclusive and habitat-specialist woody species. This uniqueness of vegetation types should be considered in terms of complementarity for the conservation of campos rupestres .